Medication adherence in the curricula of future European physicians, pharmacists and nurses – a cross-sectional survey - Hanna Gottlieb; Laura Seghers; Francisca Leiva-Fernandez; Cristina Mihaela Ghiciuc; Gaye Hafez; Maria Teresa Herdeiro; Ana Tomas Petrović; Teddy Novais; Marie P. Schneider; Alexandra Dima; Marie Ekenberg; Björn Wettermark; et al. (BMC Medical Education)
Abstract Aim Many patients are not taking their medicines. It has substantial negative medical and economic consequences for patients and healthcare systems but there is limited knowledge on how medication adherence is integrated in medical education. This study seeks to investigate to what extent students in medicine, pharmacy and nursing in Europe are taught about medication adherence. Methods A cross-sectional online survey was distributed to 731 persons teaching relevant courses across 142 European universities between February and June 2024. The survey addressed definitions of adherence and The ABC Taxonomy; methods to support adherence, methods to identify and monitor non-adherence; consequences and outcomes of non-adherence, and methods applied in teaching. They were also asked to provide links to their curricula. Responses from quantitative questions were analyzed descriptively. Word frequency and qualitative thematic analysis was used for the curricula inventory and analysis of free-text answers, respectively. Results In total, 212 participants from 114 universities in 34 countries completed the survey. Respondents agreed to similar level on the need to enhance medication adherence teaching, with 72% in pharmacy, 71% medical, and 59% agreement in nursing education. The most taught topic across educations was the clinical impact of non-adherence, according to 89% in pharmacy, 84% medical, and 76% in nursing education. The ABC Taxonomy was taught in more than half of all pharmacy (73%), nursing (60%) and medical education (52%). In the qualitative analysis of free text-answers respondents emphasized the value of early, mixed method teaching. They reported a lack of guidance in teaching medication adherence, causing inconsistency in the educational quality and depth. Time constraints were highlighted as a significant challenge, while interprofessional collaboration and use of medication adherence technologies were seen as opportunities, though not widely implemented in teaching. The curricula inventory showed a substantial variance in how medication adherence content was described. Conclusion There is a lack of consistent teaching on medication adherence in Europe, underlining the necessity to establish a unified curriculum incorporating the ABC taxonomy, and to include a more patient-centred approach to support medication adherence.